The Role of Exchange Rates in the Stock Price Development of Chemical Companies in the Visegrad Four Countries - Jana Simaḱova\'; Nikola Ruskova\' (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of the paper is to evaluate the effect of exchange rates on the stock prices of companies in the chemical industry listed on the stock exchanges in the Visegrad Four countries. The empirical analysis was performed from September 2003 to June 2016 on companies from the petrochemical and pharmaceutical industry. The effect of the exchange rate on stock prices is analyzed using Jorion's approach on monthly data. In contrast to the selected petrochemical companies, the pharmaceutical companies did not use any hedging instruments in the tested period. The effect of the exchange rate on the stock price was proved only in the case of companies from the pharmaceutical industry. This suggests that exchange rate risk could be eliminated by using hedging instruments.
Keywords: F31; G12; 330; exchange rate; firm value; exchange rate exposure; Jorion's model; chemical industry